The level of research skills of the Masters students from the point of view of the faculty members (Field study at the Faculty of Education, Tishreen University) - Ali, Wafika Salman; Alshiekh, Sarah Nizar (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of the research was to reveal the level of research skills of the master students in the Faculty of Education, Tishreen University, and the significance of the differences in the sample of the study to identify the research skills according to the research variables (department, scientific rank, years of experience in scientific supervision of the master’s thesis), The research sample consisted of (30) teaching staff members in the Faculty of Education, Tishreen University, The researcher used a questionnaire consisting of (54) items, divided into three axes (cognitive and academic skills, basic skills and preparatory skills), the concluded of The study showed that the level of research skills of the master students in the Faculty of Education, Tishreen University, from the point of view of faculty members was moderate, and there were no statistically significant differences at the level of significance (0.05) between the average estimates of faculty members in the Faculty of Education, Latex attributed to the research variables (Section, Academic rank, years of experience in the scientific supervision of the master’s thesis), The research also presented several proposals, the most important of which is the establishment of training courses to improve the scientific research skills of the students of the Faculty of Education at Tishreen University. هدف البحث إلى الكشف عن مستوى المهارات البحثية لدى طلبة الماجستير في كلية التربية بجامعة تشرين، ودلالة الفروق لدى أفراد عينة الدراسة على استبانة المهارات البحثية وفق متغيرات البحث (القسم، الرتبة العلمية، سنوات الخبرة في الإشراف العلمي على رسائل الماجستير)، واعتمدت الباحثة المنهج الوصفي، تكونت عينة البحث من (30) عضو هيئة تدريسية من كلية التربية بجامعة تشرين، وقامت الباحثة بتطبيق استبانة مؤلفة من (54) بنداً، مقسمةً إلى ثلاثة محاور (المهارات المعرفية والأكاديمية، والمهارات الأساسية، والمهارات الإعدادية)، وخلص البحث إلى أن مستوى المهارات البحثية لدى طلبة الماجستير في كلية التربية بجامعة تشرين من وجهة نظر أعضاء الهيئة التدريسية كان مستوى متوسط، وإلى عدم وجود فروق دالة إحصائياً عند مستوى الدلالة (0.05) بين متوسطات تقديرات أعضاء الهيئة التدريسية في كلية التربية بجامعة تشرين لمستوى المهارات البحثية تعزى لمتغيرات البحث (القسم، الرتبة العلمية، سنوات الخبرة في الإشراف العلمي على رسائل الماجستير)، كما قدّم البحث مقترحات عدّة، أهمها إقامة دورات تدريبية لصقل مهارات البحث العلمي لدى الطلبة الباحثين في كلية التربية بجامعة تشرين.